PENERAPAN SAK EMKM PADA UMKM STUDI KASUS DIKOTA PONTIANAK - Sianipar, Ratu Santana Dewi Pertiwi; Rafa, Wukuf Dilvan; Haryono (Universitas Lancang Kuning, 2024)
UMKM are one of the economic activities that Indonesian people always encounter and carry out. Even though UMKM have contributed to realizing a sustainable national economy, in reality there are many challenges that UMKM owners have to face, one of the challenges is in preparing financial reports. This research aims to find out whether UMKM in the city of Pontianak carry out accounting records in accordance with the standards that apply to UMKM, namely SAK EMKM. This study used descriptive qualitative method. Primary data was obtained by researchers directly by distributing questionnaires. The research results show that the application of SAK EMKM to UMKM in Pontianak is still minimal, this is due to the low level of knowledge of SAK EMKM owners regarding SAK EMKM.